The Ideal Pigeon. Narrative of Corporeality and Interspecies Relationships based on research by the Pigeon Breeding Community - Kołodziejczyk, Roksana (Hybris, 2022)
The aim of the article is to present the results of ethnographic research carried out by me in July and August 2019, devoted to the analysis of the relationship between humans and animals, which is shaped in the practices of racing pigeon breeders (such as training, feeding, crossing, supplementation or treatment). I analyzed the empirical material gathered in the environment of the members of the pigeon association and then compared it with the existing material from the magazines "Złoty gołąb" and "Dobry Lot". The analysis of the collected materials revealed the mechanisms of the breeder-pigeon relationship, showed its multifaceted nature and discovered an extremely interesting aspect related to corporeality, power and genre chauvinism. Moreover, it allowed to look at the multispecies system of connections and interactions that take place between entities directly and indirectly involved in the process of "creating" a bird, showing the relational nature of human and non-human entities.